2016
DOI: 10.1111/cas.12996
|View full text |Cite
|
Sign up to set email alerts
|

Not all epidermal growth factor receptor mutations in lung cancer are created equal: Perspectives for individualized treatment strategy

Abstract: Somatic mutations in the epidermal growth factor receptor (EGFR) gene are present in approximately 20% (in Caucasians) to 40% (in East Asians) of adenocarcinomas of the lung. Targeted therapy for these lung cancers has been established based on evidence regarding mainly common mutations; that is, exon 19 deletions (Del19) and L858R. EGFR‐tyrosine kinase inhibitors (TKI), gefitinib, erlotinib or afatinib showed high objective response rates (ORR) of approximately 60%. Several studies suggested that Del19 might … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
305
1
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 343 publications
(323 citation statements)
references
References 81 publications
(241 reference statements)
13
305
1
4
Order By: Relevance
“…have moderate sensitivities to gefitinib or erlotinib with response rate of 30%-50%. 9 In up to 60%-80% of patients treated with TKIs, the tumor regresses dramatically, but after a median time of 9-12 months, all patients develop acquired resistance to the targeted therapy. A secondary mutation, T790M, in the exon 20 of the EGFR gene is the most frequent cause of acquired resistance, which is found in 50%-60% of relapsed cases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…have moderate sensitivities to gefitinib or erlotinib with response rate of 30%-50%. 9 In up to 60%-80% of patients treated with TKIs, the tumor regresses dramatically, but after a median time of 9-12 months, all patients develop acquired resistance to the targeted therapy. A secondary mutation, T790M, in the exon 20 of the EGFR gene is the most frequent cause of acquired resistance, which is found in 50%-60% of relapsed cases.…”
Section: Resultsmentioning
confidence: 99%
“…For patients with EGFR T790M mutations, treatment with osimertinib may be effective and nazartinib (EGF816) is promising for the majority of them. 9 Thus, an accurate EGFR mutational analysis before initiation of treatment and repeat EGFR mutation testing at relapse, are now recommended in several clinical practice guidelines. 10 The incidence of EGFR mutations in NSCLC varies across different ethnicities.…”
Section: Introductionmentioning
confidence: 99%
“…In both of these two patients, first-line erlotinib provided partial response, but only 5–7 months of PFS and 8–10 months of OS from the start of EGFR-TKIs [8]. Second, a collected and retrospective data showed that first-generation EGFR-TKI provided 42 and 53% of overall response rate for S768I single mutation and compound mutations, respectively [6]. Third, in a study of 9 patients with S768I mutation at Mayo Clinic, among 4 patients with metastatic disease treated with erlotinib, one and two patients achieved partial response and stable disease, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this in vitro study, afatinib showed very low half maximal inhibitory concentration (IC 50 ) value to S768I mutation, but both gefitinib and erlotinib had high values of IC 50. Osimertinib was less sensitive to S768I mutation than afatinib [6, 11]. A Korean phase II trial showed that osimertinib achieved partial response in 3 patients of 8 with EGFR-TKI naïve S768I mutation (ORR, 37.5%) [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation